(untitled) (REMUNOM, 2025)
ABSTRACT This article aims to analyze how neuroscience knowledge can support pedagogical practices focused on reading instruction in inclusive literacy contexts. It is a qualitative, bibliographic research based on scientific publications indexed between 2022 and 2025. The analysis showed that reading involves multiple neural systems and that neurocompatible pedagogical practices—such as multisensory stimulation, phonological awareness, and visual aids—are effective in developing reading skills, especially in students with learning difficulties. The results also highlight the need for continuous teacher education and the adoption of personalized strategies tailored to different cognitive profiles. It is concluded that integrating neuroscience and education contributes to more inclusive, equitable, and evidence-based literacy. Keywords: Neuroscience. Inclusive literacy. Reading. Pedagogical practice. Education.